The Implementation Of Apriori Algorithm Methods For Predicting Project Material Purchases At CV. Padat Karya Konstruksi - Nadia Elisa Suhardi; Maryaningsih Maryaningsih; Rizka Tri Alinse (Jurnal Komputer, Informasi dan Teknologi, 2022)
In predicting the purchase of goods, there are many methods that can be used, among others, by processing purchase data using Data Mining method accompanied by Priori Algorithm based on the purchasing process carried out by the company based on the relationship between the goods purchased. By using the a priori algorithm, the company in this case is CV. Padat Karya Konstruksi can estimate the number of building materials needed by workers this is due to the large number of goods purchases at CV. Padat Karya Konstruksi to match the work. The stages of the a priori algorithm used are data transformation in tabular table form, determining the minimum value of support and minimum confidence, formation of 1-item set candidate combination pattern then counting the number of occurrences in each item set. So that it is obtained from 17 (seventeen) data, items that are often purchased are cement as much as 11 (eleven) times, split stone 8 (eight) times, and concrete sand as much as 8 (eight) times with a support value of 25% and a confidence value of 75%.